Enhancement in Polarization and Energy Density of PVDF Matrix Using Hydroxylated CeO2-NPs as Filler in Nanocomposite Thick Film - Singh V.P.; Satyarthi S.K.; Paliwal S.; Singh A.K. (My University, 2025)
PVDF is a highly explored polymer dielectric material with α-phase as paraelectric and β, γ and δ-phases as ferroelectric phases. We have investigated PVDF and its nanocomposite (PVDF/Hydroxylated-CeO2) using hydroxylated CeO2 nanoparticles (Hy-CeO2-NPs) as filler for dielectric energy storage applications. The chosen CeO2-NPs are semiconducting nanoparticles with sizes in the range of 15-20 nm. Pure and nanocomposite thick films were synthesized by solution cast method and characterized for structure, microstructure dielectric and ferroelectric properties. The X-ray diffraction analysis of the nanocomposite films reveals the formation of ferroelectric β, γ-phases and FESEM images show that the prepared films are defects free and homogenous. FTIR analysis is also done to identify the electroactive phase formation with improved ferroelectric polarization and energy storage density of the developed nanocomposites. © 2023 IEEE.